Antifungal Drug Discovery: New Theories and New Therapies - Chaminda Jayampath Seneviratne (Frontiers Research Topics, 2016)
Fungal infections such as candidoses can range from superficial mucous membrane infection to life-threatening systemic mycoses. Candida infections are a significant clinical problem globally due to rapid rise in compromised host populations including HIV/AIDS, organ transplant recipients and patients on chemotherapy. In addition, sharp increase in aging populations which are susceptible to fungal infections is expected in next few decades. Antifungal drugs are relatively difficult to develop compared to the antibacterial drugs owing to the eukaryotic nature of the cells. Therefore, only a handful of antifungal agents are currently available to treat the myriad of fungal infections. Moreover, rising antifungal resistance and host-related adverse reactions have limited the antifungal arsenal against fungal pathogens. In this research topic, we tried to update the theoretical aspects pertaining to the antifungal drug discovery i.e. proposed novel mechanisms, new drug targets and pathways. In addition, invited authors explored the new antifungal drugs derived from natural and synthetic sources which are currently under development. Contributors were encouraged to bring new insight into the antifungal drug discovery. We hope the reader may arrive at a general consensus on the possible strategies to combat ever increasing ubiquitous fungal infection in this new century.